User centered approach for designing a travel website for the elderly / Sumathi a/p Balakrishnan - Balakrishnan, Sumathi (2008)
This research focuses on designing a website using user centered approach for the elderly. Currently due to the increased shift of the elderly population around the world, it is important to give attention to development that caters to the needs of the elderly. One of the most important and beneficial developments that needs added attention is the website catered for the elderly. Currently there are problems on designs of the website which are targeted for elderly users that do not cater to their functional impairments. This is due to the ignorance of web designers to design targeting the elderly users’ capabilities. There are many productions of guidelines for Web designing but many of its points overlap and stress the same point although phrased differently (Kurniawan & Zaphiris, 2005). This research focuses on improving this situation by producing a list of 34 recommended guidelines through compiling four published guidelines. These recommended guidelines are then incorporated into the Blue Air Travels website developed for the elderly through a user centered design approach (Preece, 2002). There are four stages in this process which are, establishing requirement, design, ‘building an interactive version’ and evaluation. Elderly involvements are inevitable throughout this process and subsequently varied techniques are carried out at different stages. The process of UCD begins with establishing user interface requirement and functional requirements. Techniques such as contextual inquiry, evaluating existing travel website through task analysis and task scenarios are carried out. Stages of designing and building an interactive version are strongly interrelated. At this stage three other techniques are applied such as card sorting, low-fidelity (paper prototype) and high-fidelity (software prototype) to find usability requirements. The compiled guidelines contribute to the high-fidelity prototype. An evaluation through user testing is conducted at each version of the design. Lastly a final user testing is done on the Blue Air Travels website. The result of the final user testing shows Blue Air Travel website prototype shows a satisfactory result. The positive response from the elderly on the evaluation of the Blue Air Travels website shows that compliance of the websites to the recommended guidelines. Besides that the user centered methodologies enables the identification of the elderly usability problems and resolves the problems they are facing.